Microstructure, leakage current and dielectric tunability properties of W6+:Na0.5Bi0.5TiO3/Fe3+:Na0.5Bi0.5TiO3 bilayered thin film. (5th December 2016) - Bi, B.; Yang, C. H.; Yao, Q.; Song, J. H.; Sun, X. S.
Abstract: The bilayered Na0.5 Bi0.5 Ti0.99 W0.01 O3 /Na0.5 Bi0.5 Ti0.98 Fe0.02 O3 (NBTW/NBTFe) structure was grown on indium tin oxide/glass using a modified sol–gel process. The microstructure, and insulating and dielectric properties were investigated. X-ray diffraction indicates that the bilayered thin film is well crystallized with a phase-pure perovskite structure. The thin film shows a uniform surface without crack, and no interface is found between the NBTW/NBTFe structure. In the dielectric constant-electric field curves for dielectric measurement, abnormal loops are observed under the low electric field or high frequency. A maximum value of 35.4% for dielectric tunability is obtained when an electric field of ±500 kV/cm is applied, which can be mainly due to the good insulating characteristic with low leakage current. Furthermore, a dielectric constant of 484, dielectric loss of 0.07 as well as figure of merit of 5.1 can be observed at the frequency of 100 kHz. These findings can be taken as a base for further improving the electrical performance of NBT-based thin films.